Electrodes and secondary batteries

KR103019708B1Active Publication Date: 2026-09-15DAIKIN INDUSTRIES LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
KR1020247037984
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-05-19
Filing Date
2023-01-30
Publication Date
2026-09-15
Estimated Expiration
2043-01-30

Smart Images

  • Figure 112024125297332-PCT00001
    Figure 112024125297332-PCT00001
  • Figure 112024125297332-PCT00002
    Figure 112024125297332-PCT00002
  • Figure 112024125297332-PCT00003
    Figure 112024125297332-PCT00003
Patent Text Reader

Abstract

The electrode comprises an electrode active material layer and a polymer layer formed on the electrode active material layer, wherein the polymer layer comprises a copolymer containing fluoro monomer units and amide bond-containing monomer units and an inorganic particle.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present disclosure relates to electrodes and secondary batteries. Background Technology

[0002] Patent Document 1 describes a lithium-ion secondary battery comprising a positive electrode, a negative electrode, a polymer layer, and a lithium-ion permeable insulating layer, wherein the positive electrode comprises a positive electrode active material layer containing a positive electrode active material capable of absorbing and releasing lithium and a positive electrode current collector, the negative electrode comprises a negative electrode active material layer formed by a vapor phase method and containing an alloy-based negative electrode active material and a negative electrode current collector, the polymer layer is formed on the surface of the negative electrode active material layer and contains a first polymer and a first inorganic oxide particle, and the lithium-ion permeable insulating layer is disposed to be interposed between the positive electrode and the negative electrode.

[0003] Patent document 2 describes a composition characterized by comprising an inorganic filler, a copolymer of a polymerizable vinyl compound having an amide bond with a fluoromonomer, and a solvent. Prior art literature

[0004] Japanese Patent Publication No. 2010-250968, International Publication No. 2020 / 054210 The problem to be solved

[0005] The present disclosure aims to provide an electrode that enables a secondary battery in which storage capacity is unlikely to decrease even after storage at high temperatures and resistance is unlikely to increase even after repeated charging and discharging. means of solving the problem

[0006] According to a first aspect of the present disclosure, an electrode is provided having an electrode active material layer and a polymer layer formed on the electrode active material layer, wherein the polymer layer comprises a copolymer containing fluoro monomer units and amide bond-containing monomer units and an inorganic particle. Effects of the invention

[0007] According to the present disclosure, an electrode can be provided that enables a secondary battery in which the storage capacity is unlikely to decrease even after storage at high temperatures and the resistance is unlikely to increase even after repeated charging and discharging. Specific details for implementing the invention

[0008] Specific embodiments of the present disclosure will be described in detail below, but the present disclosure is not limited to the following embodiments.

[0009] The electrode of the present disclosure comprises an electrode active material layer and a polymer layer formed on the electrode active material layer.

[0010] Patent Document 1 describes a lithium-ion secondary battery using an alloy-based negative electrode active material, wherein a polymer layer containing a first polymer and a first inorganic oxide particle is formed on the surface of a negative electrode active material layer, thereby obtaining a lithium-ion secondary battery with excellent battery performance such as charge-discharge cycle characteristics and output characteristics, a long service life, very little degradation of battery characteristics even when the number of charge-discharge cycles increases, and high safety against internal short circuits.

[0011] However, it was found that in the method of forming a polymer layer containing a first polymer and a first inorganic oxide particle on the surface of a negative electrode active material layer as proposed in Patent Document 1, the storage capacity tends to decrease when stored at high temperatures, and furthermore, the increase in resistance after repeated charging and discharging of the secondary battery cannot be sufficiently suppressed.

[0012] Accordingly, we have carefully examined a means to obtain a secondary battery in which the storage capacity is unlikely to decrease even after storage at high temperatures and the resistance is unlikely to increase even after repeated charging and discharging. By forming a polymer layer containing a copolymer containing a fluoro monomer unit and an amide bond-containing monomer unit and an inorganic particle on an electrode active material layer, we have found that an electrode can be obtained in which the storage capacity is unlikely to decrease even after storage at high temperatures and the resistance is unlikely to increase even after repeated charging and discharging.

[0013] That is, the electrode of the present disclosure is an electrode comprising an electrode active material layer and a polymer layer formed on the electrode active material layer, and since the polymer layer contains a copolymer containing a fluoro monomer unit and an amide bond-containing monomer unit and an inorganic particle, by using the electrode of the present disclosure as an electrode of a secondary battery, it is possible to obtain a secondary battery in which the storage capacity is difficult to decrease even after storage at high temperatures and the resistance is difficult to increase even after repeated charging and discharging.

[0014] Hereinafter, embodiments of the electrode of the present disclosure will be described in more detail.

[0015] The electrode of the present disclosure comprises an electrode active material layer and a polymer layer formed on the electrode active material layer.

[0016] (Polymer layer)

[0017] The polymer layer of the electrode of the present disclosure contains a copolymer and inorganic particles and is formed on the electrode active material layer. The polymer layer may be formed directly on the electrode active material layer without passing through another layer, or it may be formed on the electrode active material layer through another layer; however, since sufficient effects can be obtained by forming the polymer layer, it is preferable that it be formed directly on the electrode active material layer without passing through another layer.

[0018] (Copolymer)

[0019] The copolymer included in the polymer layer contains fluoromonomer units and amide bond-containing monomer units.

[0020] As for fluoromonomers that form fluoromonomer units, (1) sp 2 Examples include an olefin having a fluorine atom bonded to a hybrid carbon atom, (2) a monomer represented by the general formula: CH2=CX-COORf (wherein X is Cl, H or an alkyl group, and Rf is a fluoroalkyl group), (3) a monomer represented by the general formula: CH2=CH-Rf (wherein Rf is a fluoroalkyl group), and (4) a monomer represented by the general formula: CH2=CH-ORf (wherein Rf is a fluoroalkyl group).

[0021] As for the alkyl group, an alkyl group having 1 to 3 carbon atoms can be used, and a methyl group is preferred.

[0022] As for the fluoroalkyl group, a straight-chain or branched fluoroalkyl group having 1 to 12 carbon atoms is preferred.

[0023] As for the fluoromonomer, a fluorine atom bonded to a carbon atom constituting the polymer main chain can be introduced into the copolymer, and thereby, the performance of the secondary battery can be further improved, so (1) is preferred, and vinylidene fluoride, trifluoroethylene, tetrafluoroethylene, hexafluoropropylene, chlorotrifluoroethylene, monofluoroethylene, trifluorostyrene, and, general formula: CX2=CXRf 1 (in the formula, X is independently H or F, at least one of X is F, Rf 1 It is more preferable that it be at least one selected from the group consisting of fluoromonomers represented by straight-chain or branched fluoroalkyl groups having 1 to 12 carbon atoms.

[0024] As for the fluoro monomer, since it can further improve the performance of the secondary battery, it is more preferable to be at least one selected from the group consisting of tetrafluoroethylene, hexafluoropropylene, chlorotrifluoroethylene, and 2,3,3,3-tetrafluoropropene, and tetrafluoroethylene is particularly preferred.

[0025] The amide-containing monomer forming the amide-containing monomer unit contains an amide bond and a polymerizable vinyl group. The amide bond refers to a bond between a carbonyl group and a nitrogen atom. Examples of the polymerizable vinyl group include a vinyl group, an allyl group, a vinyl ether group, a vinyl ester group, an acrylic group, etc.

[0026] Examples of monomers containing amide bonds include N-vinyllactam compounds such as N-vinyl-β-propiolactam, N-vinyl-2-pyrrolidone, N-vinyl-2-piperidone, and N-vinyl-heptolactam; non-cyclic N-vinylamide compounds such as N-vinylformamide and N-methyl-N-vinylacetamide; non-cyclic N-allylamide compounds such as N-allyl-N-methylformamide and allylurea; N-allylactam compounds such as 1-(2-propenyl)-2-pyrrolidone; and acrylamide compounds such as (meth)acrylamide, N,N-dimethylacrylamide, and N-isopropylacrylamide.

[0027] As an amide-linked monomer, also,

[0028]

[0029] (during food, R 11 and R 12 A compound represented independently by H or an alkyl group having 1 to 10 carbon atoms,

[0030]

[0031] (during food, R 11 and R 12 Examples include compounds represented independently by H or an alkyl group having 1 to 10 carbon atoms.

[0032] As for the monomer containing an amide bond, a monomer having a lactam ring is preferred. As for the lactam ring, it is not particularly limited as long as it is a ring formed by an amide bond and a carbon atom, and it may be a single ring or a polycyclic ring, but it is preferred to be a single ring. In addition, the lactam ring may have any substituent. Examples of lactam rings include α-lactam rings, β-lactam rings, γ-lactam rings, δ-lactam rings, ε-caprolactam rings, ω-heptalactam rings, etc.

[0033] A monomer containing an amide bond may have a structure in which the remaining atomic group, after removing one or more hydrogen atoms bonded to a carbon or nitrogen atom forming a lactam ring, is directly or indirectly bonded to a polymerizable vinyl group. For example, a monomer containing an amide bond may have a structure in which the remaining atomic group, after removing one hydrogen atom bonded to a carbon or nitrogen atom forming a lactam ring, is bonded to a vinyl group or an allyl group.

[0034] As the amide bond-containing monomer can further improve the performance of the secondary battery, among them, at least one selected from the group consisting of N-vinyl-β-propiolactam, N-vinyl-2-pyrrolidone, N-vinyl-2-piperidone, N-vinyl-ε-caprolactam, and N-vinyl-heptolactam is preferred, at least one selected from the group consisting of N-vinyl-2-pyrrolidone, N-vinyl-2-piperidone, and N-vinyl-ε-caprolactam is more preferred, and N-vinyl-2-pyrrolidone is even more preferred.

[0035] The copolymer may contain other monomer units in addition to the fluoromonomer units and the amide-linked monomer units. The other monomers are not particularly limited as long as they are monomers capable of copolymerizing with the fluoromonomers and the amide-linked monomers. Examples of other monomer units include vinyl ester monomer units, vinyl ether monomer units, (meth)acrylic monomer units having polyethylene glycol in a side chain, vinyl monomer units having polyethylene glycol in a side chain, (meth)acrylic monomer units having long-chain hydrocarbon groups, vinyl monomer units having long-chain hydrocarbon groups, etc.

[0036] Since the content of fluoromonomer units in the copolymer can further improve the performance of the secondary battery, it is preferable that the content of fluoromonomer units be 75 to 7 mol% with respect to the total monomer units, and the content of amide bond-containing monomer units in the copolymer be 25 to 93 mol% with respect to the total monomer units.

[0037] The content of fluoromonomer units of the copolymer is more preferably 60 mol% or less, even more preferably 55 mol% or less, particularly preferably 50 mol% or less, most preferably 45 mol% or less, more preferably 15 mol% or more, even more preferably 20 mol% or more, particularly preferably 35 mol% or more, and most preferably 40 mol% or more.

[0038] The content of monomer units containing amide bonds in the copolymer is more preferably 40 mol% or more, even more preferably 45 mol% or more, particularly preferably 50 mol% or more, most preferably 55 mol% or more, more preferably 85 mol% or less, even more preferably 80 mol% or less, particularly preferably 65 mol% or less, and most preferably 60 mol% or less.

[0039] The content of other monomer units of the copolymer is preferably 50 mol% or less, more preferably 35 mol% or less, even more preferably 25 mol% or less, more preferably 15 mol% or less, particularly preferably 5 mol% or less, and preferably 0 mol% or more.

[0040] In addition, the copolymer may substantially be a copolymer containing only fluoromonomer units and amide bond-containing monomer units.

[0041] The composition of the copolymer is, for example, 1 H-NMR and 19 It can be measured by F-NMR.

[0042] The weight-average molecular weight of the copolymer (in polystyrene equivalent) is preferably 10,000 to 500,000, more preferably 15,000 or more, even more preferably 20,000 or more, particularly preferably 30,000 or more, and more preferably 400,000 or less, as this can further improve the performance of the secondary battery. The weight-average molecular weight can be measured by gel permeation chromatography (GPC) using dimethylformamide as a solvent.

[0043] (Method for manufacturing copolymer)

[0044] A copolymer can be suitably produced by a manufacturing method of polymerizing a fluoro monomer, an amide-linked monomer, and, if necessary, other monomers in a reactor.

[0045] As a polymerization method, methods such as suspension polymerization, emulsion polymerization, and solution polymerization may be employed.

[0046] In addition, since it is possible to produce copolymers having a high molecular weight, a polymerization method using a fluorine-containing solvent is preferred among various polymerization methods. The copolymer can be suitably produced, for example, by a manufacturing method in which at least a fluoro monomer and an amide-linked monomer are polymerized in a fluorine-containing solvent to obtain a copolymer.

[0047] As fluorine-containing solvents, hydrochlorofluoroalkanes such as CH3CClF2, CH3CCl2F, CF3CF2CCl2H, CF2ClCF2CFHCl; chlorofluoroalkanes such as CF2ClCFClCF2CF3, CF3CFClCFClCF3; perfluoroalkanes such as perfluorocyclobutane, CF3CF2CF2CF3, CF3CF2CF2CF2CF3, CF3CF2CF2CF2CF2CF3; CF2HCF2CF2CF2H, CF3CFHCF2CF2CF3, CF3CF2CF2CF2CF2H, CF3CF2CFHCF2CF3, CF3CFHCFHCF2CF3, CF2HCF2CF2CF2CF2H, CF2HCFHCF2CF2CF3, CF3CF2CF2CF2CF2CF2H, CF3CH(CF3)CF3CF2CF3, Hydrofluorocarbons such as CF3CF(CF3)CFHCF2CF3, CF3CF(CF3)CFHCFHCF3, CF3CH(CF3)CFHCF2CF3, CF2HCF2CF2CF2CF2CF2H, CF3CF2CF2CF2CH2CH3, CF3CH2CF2CH3; Examples include (perfluoroalkyl)alkyl ethers such as F(CF2)4OCH3, F(CF2)4OC2H5, (CF3)2CFOCH3, F(CF2)3OCH3, etc.; hydrofluoroalkyl ethers such as CF3CH2OCF2CHF2, CHF2CF2CH2OCF2CHF2, CF3CF2CH2OCF2CHF2, etc.

[0048] As for the fluorine-containing solvent, at least one selected from the group consisting of hydrofluorocarbons, (perfluoroalkyl)alkyl ethers and hydrofluoroalkyl ethers is preferred because it can produce a copolymer having an even higher molecular weight, and hydrofluoroalkyl ethers are more preferred.

[0049] Among the fluorine-containing solvents, at least one selected from the group consisting of CF3CH2CF2CH3, CF3CH2OCF2CHF2, CHF2CF2CH2OCF2CHF2, and CF3CF2CH2OCF2CHF2 is preferred, and CF3CH2OCF2CHF2 is more preferred.

[0050] In the above polymerization, a polymerization initiator, a surfactant, and a chain transfer agent may be used, and each may be a conventionally known one.

[0051] As a polymerization initiator, a radical polymerization initiator may be used. As a polymerization initiator, for example,

[0052] Dialkyl peroxycarbonates such as dinormal propyl peroxydicarbonate, diisopropyl peroxydicarbonate, and disec-butyl peroxydicarbonate;

[0053] Peroxyesters such as t-butylperoxyisobutyrate, t-butylperoxypivalate, t-hexylperoxy2-ethylhexanoate, t-butylperoxy-2-ethylhexanoate, 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate, t-amylperoxypivalate;

[0054] Dialkyl peroxides such as dit-butyl peroxide;

[0055] Di[fluoro(or fluorochloro)acyl]peroxides;

[0056] The back can be cited as a representative example.

[0057] Examples of di[fluoro(or fluorochloro)acyl]peroxides include diacyl peroxides represented by [(RfCOO)-]2 (where Rf is a perfluoroalkyl group, ω-hydroperfluoroalkyl group, or fluorochloroalkyl group).

[0058] As di[fluoro(or fluorochloro)acyl]peroxides, for example, di(ω-hydro-dodecafluoroheptanoyl)peroxide, di(ω-hydro-tetradecafluorooctanoyl)peroxide, di(ω-hydro-hexadecafluorononanoyl)peroxide, di(perfluorobutyryl)peroxide, di(perfluorooropaleryl)peroxide, di(perfluorohexanoyl)peroxide, di(perfluoroheptanoyl)peroxide, di(perfluorooctanoyl)peroxide, di(perfluorononanoyl)peroxide, di(ω-chloro-hexafluorobutyryl)peroxide, di(ω-chloro-decafluorohexanoyl)peroxide, di(ω-chloro-tetradecafluorooctanoyl)peroxide, ω-hydro-dodecafluoroheptanoyl-ω-

[0059] Examples include hydrohexadecafluorononanoyl-peroxide, ω-chloro-hexafluorobutyryl-ω-chloro-decafluorohexanoyl-peroxide, ω-hydrododecafluoroheptanoyl-perfluorobutyryl-peroxide, di(dichloroheptafluorobutanoyl)peroxide, di(trichlorooctafluorohexanoyl)peroxide, di(tetrachloroundecafluorooctanoyl)peroxide, di(pentachlorotetradecafluorodecanoyl)peroxide, di(undecachlorotriacontafluorodocosanoyyl)peroxide, etc.

[0060] By polymerizing in the presence of a chain transfer agent, the solution viscosity, weight-average molecular weight, etc. of the copolymer obtained can be appropriately adjusted. Examples of chain transfer agents include hydrocarbons such as ethane, isopentane, n-hexane, and cyclohexane; aromatics such as toluene and xylene; ketones such as acetone; acetic acid esters such as ethyl acetate and butyl acetate; alcohols such as methanol and ethanol; mercaptans such as methyl mercaptan; and halogenated hydrocarbons such as carbon tetrachloride, chloroform, methylene chloride, and methyl chloride.

[0061] The polymerization temperature is not particularly limited, but is preferably 0 to 95°C and more preferably 15 to 95°C in terms of the polymerization rate and the cost of heating.

[0062] The polymerization pressure is not particularly limited, but is preferably 0.3 to 1.5 MPaG in terms of the polymerization rate and the internal pressure of the reactor, more preferably 0.4 MPaG or higher, and more preferably 1.0 MPaG or lower.

[0063] After the polymerization is finished, if the copolymer is obtained as a slurry, the polymer can be recovered by removing the slurry from the reactor, washing it, and drying it.

[0064] (Inorganic particles)

[0065] As for the inorganic particles included in the polymer layer, inorganic particles containing at least one element selected from the group consisting of Mg, Al, Si, Ti, Zr, and Ba are preferred. The inorganic particles are suitably inorganic particles (except for electrode active materials).

[0066] As for the inorganic particles, at least one selected from the group consisting of metal oxide particles and metal hydroxide particles is preferred. Additionally, as for the inorganic particles, metal oxide particles containing at least one element selected from the group consisting of Mg, Al, Si, Ti, Zr, and Ba are more preferred.

[0067] As for the metal oxide particles, at least one particle selected from the group consisting of MgO, Al2O3, SiO2, TiO2, ZrO2, and BaO is preferred.

[0068] As for the metal hydroxide particles, at least one particle selected from the group consisting of Mg(OH)2, Al(OH)3, and Zr(OH)4 is preferred.

[0069] Among the inorganic particles, at least one particle selected from the group consisting of MgO, Al2O3, SiO2, and ZrO2 is preferred, and Al2O3 particles are more preferred.

[0070] The average particle size of the inorganic particles is preferably 25 μm or less, more preferably 10 μm or less, even more preferably 5 μm or less, particularly preferably 1 μm or less, and preferably 0.02 μm or more. The average particle size of the inorganic particles is a value obtained by measuring using a transmission electron microscope, a laser particle size distribution measuring device, etc.

[0071] In the polymer layer, the content ratio of copolymer to inorganic particles [(copolymer) / (inorganic particles)] is, in mass ratio, preferably 0.1 / 99.9 to 49.9 / 50.1, more preferably 1 / 99 or more, even more preferably 5 / 95 or more, particularly preferably 10 / 90 or more, more preferably 45 / 55 or less, and even more preferably 40 / 60 or less.

[0072] (Method for forming a polymer layer)

[0073] The polymer layer can be formed by, for example, by preparing a composition containing a copolymer and inorganic particles and coating the composition onto an electrode active material layer.

[0074] The coating method is not particularly limited as long as it is a method capable of covering the surface of the electrode active material layer with a polymer layer formed from the composition, but for example, a method of applying the composition onto the electrode active material layer and drying the coating film may be cited. More specifically, as a coating method, a method of roll-coating the composition onto the electrode active material layer, a method of dipping the electrode active material layer into the composition, or a method of coating the electrode active material layer with the composition and immersing it in a suitable coagulation solution may be cited. In addition, a film may be produced using the composition, and the obtained film and the electrode active material layer may be laminated by a method such as lamination. As a method of producing a film using the composition, an example method may be to cast the composition onto a film having a smooth surface, such as a polyester film or an aluminum film, and then peel it off.

[0075] A composition containing copolymers and inorganic particles also preferably contains a solvent.

[0076] As a solvent, for example, water; nitrogen-containing organic solvents such as N-methyl-2-pyrrolidone, N,N-dimethylacetamide, and dimethylformamide; ketone solvents such as acetone, methyl ethyl ketone, cyclohexanone, and methyl isobutyl ketone; ester solvents such as ethyl acetate and butyl acetate; ether solvents such as tetrahydrofuran, dioxane, ethyl cellosolve, methyl cellosolve, deglame, and triglame; aromatic hydrocarbon solvents such as xylene, toluene, and solvent naphtha; and aliphatic hydrocarbon solvents such as n-pentane, n-hexane, n-heptane, n-octane, n-nonane, n-decane, n-undecane, n-dodecane, and mineral spirits; Examples include fluorine-containing solvents such as CF3CH2CF2CH3, CF3CH2OCF2CHF2, CHF2CF2CH2OCF2CHF2, and CF3CF2CH2OCF2CHF2; and mixed solvents thereof.

[0077] (Electrode active material layer)

[0078] The electrode active material layer may contain an electrode active material and a binder. The electrode of the present disclosure may be used as a positive electrode and may be used as a negative electrode. Accordingly, the electrode active material may be a positive electrode active material or a negative electrode active material. Furthermore, the positive electrode may comprise a positive electrode active material layer containing a positive electrode active material and a binder, and a polymer layer formed on the positive electrode active material layer. The negative electrode may comprise a negative electrode active material layer containing a negative electrode active material and a binder, and a polymer layer formed on the negative electrode active material layer.

[0079] The electrode typically comprises a current collector, and the electrode active material layer is formed on the current collector. The electrode active material layer may be formed on one side of the current collector or on both sides. When the electrode active material layer is formed on both sides of the current collector, the polymer layer may be formed only on the electrode active material layer on one side, or the polymer layer may be formed on both electrode active material layers.

[0080] The embodiments of the positive and negative poles will be explained in more detail below.

[0081] (Straight play)

[0082] The positive electrode comprises a positive electrode active material layer containing a positive electrode active material and a binder, and a polymer layer formed on the positive electrode active material layer. By forming a polymer layer containing a copolymer containing fluoro monomer units and amide bond-containing monomer units and inorganic particles on the positive electrode active material layer, a secondary battery can be obtained in which the storage capacity is difficult to decrease even after storage at high temperatures and the resistance is difficult to increase even after repeated charging and discharging.

[0083] (Positive electrode active material)

[0084] As for the positive electrode active material, there are no particular restrictions as long as it is capable of electrochemically absorbing and releasing lithium ions.

[0085] As a positive electrode active material, a positive electrode active material containing at least one alkali metal selected from the group consisting of Li, Na, and K is preferred, and a positive electrode active material containing at least one alkali metal selected from the group consisting of Li, Na, and K and at least one metal selected from the group consisting of Fe, Ni, Mn, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si, and Ge is more preferred.

[0086] As a positive electrode active material, it is preferable to use a material containing lithium and at least one transition metal, such as a lithium transition metal composite oxide or a lithium-containing transition metal phosphate compound.

[0087] As the transition metal of the lithium transition metal composite oxide, V, Ti, Cr, Mn, Fe, Co, Ni, Cu, etc. are preferred. Specific examples of lithium transition metal composite oxides include lithium-cobalt composite oxides such as LiCoO2, lithium-nickel composite oxides such as LiNiO2, lithium-manganese composite oxides such as LiMnO2, LiMn2O4, Li2MnO3, etc., and those in which some of the transition metal atoms forming the main component of these lithium transition metal composite oxides are substituted with other metals such as Al, Ti, V, Cr, Mn, Fe, Co, Li, Ni, Cu, Zn, Mg, Ga, Zr, Si, etc. Examples of the above-mentioned substitutes include lithium-nickel-manganese composite oxides, lithium-nickel-cobalt-aluminum composite oxides, lithium-nickel-cobalt-manganese composite oxides, lithium-manganese-aluminum composite oxides, lithium-titanium composite oxides, etc. More specifically, LiNiO . 5Mn0 . 5O2, LiNi 0.85 Co 0.10 Al 0.05 O2, LiNi0 . 33 Co0 . 33 Mn0 .33 O2, LiNi0 . 5Mn0 . 3Co0 . 2O2, LiNi0 . 6Mn0 . 2Co0 . 2O2, LiNi 0.8 Mn 0.1 Co 0.1 O2, LiMn1 . 8Al0 . 2O4, LiMn1 . 5Ni0 . 5O4, Li4Ti5O 12 , LiNi0 . 82 Co0 . 15 Al0 . 03 Examples include O2.

[0088] As the transition metal of the lithium-containing transition metal phosphate compound, V, Ti, Cr, Mn, Fe, Co, Ni, Cu, etc. are preferred, and specific examples of the lithium-containing transition metal phosphate compound include, for instance, iron phosphates such as LiFePO4, Li3Fe2(PO4)3, LiFeP2O7, cobalt phosphates such as LiCoPO4, and those in which some of the transition metal atoms that form the main component of these lithium transition metal phosphate compounds are substituted with other metals such as Al, Ti, V, Cr, Mn, Fe, Co, Li, Ni, Cu, Zn, Mg, Ga, Zr, Nb, Si, etc.

[0089] In particular, in terms of high voltage, high energy density, or charge / discharge cycle characteristics, LiCoO2, LiNiO2, LiMn2O4, LiNiO . 82 Co0 . 15 Al0 . 03 O2, LiNi0 . 33 Mn0 . 33 Co0 . 33 O2, LiNi0 .5Mn0 . 3Co0 . 2O2, LiNi 0.6 Mn 0.2 Co 0.2 O2, LiNi 0.8 Mn 0.1 Co 0.1 O2 and LiFePO4 are preferred.

[0090] (bookbinder)

[0091] As a binder, a polymer (except for copolymers containing fluoromonomer units and monomer units containing amide bonds) may be used.

[0092] As for the binder, any material that is safe for the solvent or electrolyte used in the manufacture of the electrode may be used, and examples include polyvinylidene fluoride, polytetrafluoroethylene, vinylidene fluoride-tetrafluoroethylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-tetrafluoroethylene-hexafluoropropylene copolymer, polyethylene, polypropylene, styrene-butadiene rubber, isoprene rubber, butadiene rubber, ethylene-acrylic acid copolymer, ethylene-methacrylic acid copolymer, etc.

[0093] (Challenge)

[0094] The positive electrode active material layer may also contain a conductive material. Examples of conductive materials include carbon materials such as graphite, carbon black, carbon nanotubes, carbon fibers, and acetylene black.

[0095] As for the content of each component in the positive electrode active material layer, when the mass of the electrode active material layer is 100 mass%, it is preferable that the content of the positive electrode active material is 80.0 to 99.8 mass%, the content of the conductive material is 0.1 to 10.0 mass%, and the content of the binder is 0.1 to 10.0 mass%.

[0096] The positive electrode typically further comprises a positive electrode current collector, and a positive electrode active material layer is formed on the positive electrode current collector. The positive electrode active material layer may be formed on one side of the positive electrode current collector or on both sides. When the positive electrode active material layer is formed on both sides of the positive electrode current collector, the polymer layer may be formed only on the positive electrode active material layer on one side, or the polymer layer may be formed on both positive electrode active material layers.

[0097] As the material for the positive electrode current collector, metals such as aluminum, titanium, or tantalum, or alloys thereof, may be used. Among these, aluminum or an alloy thereof is preferred.

[0098] The method for forming the positive electrode active material layer can be conventional. For example, a binder, a thickener, a conductive material, a solvent, etc., are added to the positive electrode active material to form a slurry-type positive electrode composite, and this is applied to a current collector, dried, and then pressed to increase density.

[0099] Examples of thickeners include carboxymethylcellulose, methylcellulose, hydroxymethylcellulose, ethylcellulose, polyvinyl alcohol, starch oxide, starch phosphorylated, casein, etc.

[0100] As a solvent for the positive electrode composite, examples include solvents similar to those that may be contained in the composition for forming the polymer layer.

[0101] (Polar)

[0102] The negative electrode comprises a negative electrode active material layer containing a negative electrode active material and a binder, and a polymer layer formed on the negative electrode active material layer. By forming a polymer layer containing a copolymer containing fluoro monomer units and amide bond-containing monomer units and inorganic particles on the negative electrode active material layer, a secondary battery can be obtained in which the storage capacity is difficult to decrease even after storage at high temperatures and the resistance is difficult to increase even after repeated charging and discharging.

[0103] (Negative electrode active material)

[0104] Examples of negative electrode active materials include carbonaceous materials capable of absorbing and releasing lithium ions, such as thermal decomposition products of organic matter under various thermal decomposition conditions, artificial graphite, and natural graphite; metal oxide materials capable of absorbing and releasing lithium ions, such as tin oxide and silicon oxide; lithium metal; and various lithium alloys. Two or more of these negative electrode active materials may be used in combination.

[0105] As a negative electrode active material, a negative electrode active material containing a carbonaceous material, or a negative electrode active material containing a compound containing at least one element selected from the group consisting of Si, Sn, V, Nb, and Ti is preferred.

[0106] Examples of compounds containing at least one element selected from the group consisting of Si, Sn, V, Nb, and Ti include lithium alloys containing at least one element selected from the group consisting of Si, Sn, V, Nb, and Ti and lithium, and metal oxides containing at least one element selected from the group consisting of Si, Sn, V, Nb, and Ti.

[0107] As a carbonaceous material,

[0108] (1) Natural graphite,

[0109] (2) Artificial carbonaceous material and artificial graphite material; Carbonaceous materials {e.g., coal-based coke, petroleum-based coke, coal-based pitch, petroleum-based pitch, or oxidized versions of these pitches; needle coke, pitch coke, and carbon materials obtained by partially graphitizing them; thermal decomposition products of organic materials such as furnace black, acetylene black, and pitch-based carbon fibers; carbonizable organic materials (e.g., coal tar pitch ranging from soft to hard pitch, or coal-based heavy oils such as dry distillation liquefied oil, atmospheric residue, vacuum residue, ethylene tar isocratic heavy oil produced as a byproduct during the thermal decomposition of crude oil, naphtha, etc.; also aromatic hydrocarbons such as acenaphtylene, decarycyclene, anthracene, and phenanthrene; N-ring compounds such as phenazine and acridine; S-ring compounds such as thiophene and bithiophene; polyphenylenes such as biphenyl and terphenyl; polyvinyl chloride, polyvinyl alcohol, and polyvinyl butyral; and insolubilization of these A carbonaceous material obtained by heat-treating at least once in a range of 400 to 3200°C, wherein {a processed product, organic polymers containing nitrogen such as polyacrylonitrile and polypyrrole, organic polymers containing sulfur such as polythiophene and polystyrene, natural polymers such as polysaccharides represented by cellulose, lignin, mannan, polygalacturonic acid, chitosan, and saccharose, thermoplastic resins such as polyphenylene sulfide and polyphenylene oxide, thermosetting resins such as furfuryl alcohol resin, phenol-formaldehyde resin, and imide resin} and their carbides, or a solution obtained by dissolving a carbonizable organic material in a low-molecular-weight organic solvent such as benzene, toluene, xylene, quinoline, and n-hexane, and their carbides}.

[0110] (3) A carbonaceous material having a negative electrode active material layer composed of at least two different types of carbonaceous materials and / or having an interface in contact with the other types of carbonaceous materials,

[0111] (4) A carbonaceous material having a negative electrode active material layer composed of at least two different orientations and / or having an interface in contact with the carbonaceous material of the other orientation.

[0112] It is desirable to select from this as it has a good balance of initial irreversible capacity and high current density charge / discharge characteristics.

[0113] (bookbinder)

[0114] As a binder, a polymer (except for copolymers containing fluoromonomer units and monomer units containing amide bonds) may be used. As a binder, the same as the binder that may be contained in the positive electrode active material layer may be used.

[0115] As for the content of each component in the negative electrode active material layer, when the mass of the negative electrode active material layer is 100 mass%, it is preferable that the content of the negative electrode active material is 99.9 to 80.0 mass% and the content of the binder is 0.1 to 20.0 mass%.

[0116] The negative electrode typically further comprises a negative electrode current collector, and a negative electrode active material layer is formed on the negative electrode current collector. The negative electrode active material layer may be formed on one side of the negative electrode current collector or on both sides. If the negative electrode active material layer is formed on both sides of the negative electrode current collector, the polymer layer may be formed only on the negative electrode active material layer on one side, or the polymer layer may be formed on both negative electrode active material layers.

[0117] Examples of materials for the negative electrode current collector include copper, nickel, or stainless steel. Among these, copper is preferred due to its ease of processing into a thin film and its cost.

[0118] The method for forming the negative electrode active material layer can be conventional. For example, a method may be used in which a binder, a thickener, a conductive material, a solvent, etc. are added to a negative electrode active material to form a slurry-type negative electrode composite, which is then applied to a current collector, dried, and then pressed to increase density.

[0119] As a thickening agent, the same as the thickening agent that can be used to form the positive electrode active material layer can be cited.

[0120] Examples of conductive materials for the negative electrode include metallic materials such as copper or nickel; and carbon materials such as graphite and carbon black.

[0121] As a solvent for the negative electrode composite, examples include solvents similar to those that may be contained in the composition for forming the polymer layer.

[0122] (Uses of electrodes)

[0123] The electrode of the present disclosure can be used in an electrochemical device. Examples of electrochemical devices include batteries such as secondary batteries and capacitors. The battery may be a primary battery, a storage battery (secondary battery), or a storage element. The battery may be a non-aqueous electrolyte battery. Non-aqueous electrolyte batteries include all batteries equipped with an electrolyte and a power generation element. Examples of non-aqueous electrolyte batteries include lithium-ion primary batteries, lithium-ion secondary batteries, nickel-hydrogen batteries, lithium-ion capacitors, electric double-layer capacitors, etc.

[0124] (Secondary battery)

[0125] The electrode of the present disclosure can be particularly suitably used as an electrode for a secondary battery. Among the secondary batteries, a lithium-ion secondary battery is particularly preferred.

[0126] Secondary batteries are,

[0127] A secondary battery having a positive electrode, a negative electrode and a non-aqueous electrolyte, and having the electrode of the present disclosure as the positive electrode,

[0128] A secondary battery having a positive electrode, a negative electrode and a non-aqueous electrolyte, and having the electrode of the present disclosure as the negative electrode,

[0129] A secondary battery comprising a positive electrode, a negative electrode, and a non-aqueous electrolyte, wherein the electrode of the present disclosure is provided as the positive electrode and the electrode of the present disclosure is provided as the negative electrode.

[0130] Any of these forms is acceptable.

[0131] As a non-aqueous electrolyte, a known electrolyte salt dissolved in a known organic solvent for dissolving electrolyte salts may be used.

[0132] As an organic solvent for dissolving electrolyte salts, one or more types of hydrocarbon solvents such as propylene carbonate, ethylene carbonate, butylene carbonate, γ-butyrolactone, 1,2-dimethoxyethane, 1,2-diethoxyethane, dimethyl carbonate, diethyl carbonate, ethylmethyl carbonate, vinylene carbonate, etc., and fluorine-based solvents such as fluoroethylene carbonate, fluoroether, fluorinated carbonate, etc., may be used, although not specifically limited. Any conventionally known electrolyte may also be used, and LiClO4, LiAsF6, LiPF6, LiBF4, LiCl, LiBr, CH3SO3Li, CF3SO3Li, cesium carbonate, etc. may be used.

[0133] The shape of the secondary battery is arbitrary, and examples include cylindrical, prismatic, laminated, coin, and large shapes. In addition, the shape and configuration of the positive electrode, negative electrode, and separator can be changed according to the shape of each battery.

[0134] Although embodiments have been described above, it will be understood that various changes in form or detail are possible without departing from the intent and scope of the patent claims.

[0135] <1> According to the first aspect of the present disclosure,

[0136] An electrode is provided having an electrode active material layer and a polymer layer formed on the electrode active material layer, wherein the polymer layer comprises a copolymer containing fluoro monomer units and amide bond-containing monomer units and inorganic particles.

[0137] <2> According to a second aspect of the present disclosure,

[0138] An electrode according to a first aspect is provided, wherein the fluoromonomer is at least one selected from the group consisting of tetrafluoroethylene, hexafluoropropylene, chlorotrifluoroethylene, and 2,3,3,3-tetrafluoropropene.

[0139] <3> According to a third aspect of the present disclosure,

[0140] An electrode is provided according to a first or second aspect having a lactam ring, wherein the amide bond-containing monomer is provided.

[0141] <4> According to the fourth aspect of the present disclosure,

[0142] An electrode is provided according to any one of the first to third aspects, wherein the amide-linked monomer is N-vinyl-2-pyrrolidone.

[0143] <5> According to the fifth aspect of the present disclosure,

[0144] An electrode according to any one of the first to fourth aspects is provided, wherein the content of the fluoromonomer unit of the copolymer is 75 to 7 mol% with respect to the total monomer unit, and the content of the amide bond-containing monomer unit of the copolymer is 25 to 93 mol% with respect to the total monomer unit.

[0145] <6> According to the sixth aspect of the present disclosure,

[0146] An electrode according to any one of the first to fifth aspects is provided, wherein the inorganic particles contain at least one element selected from the group consisting of Mg, Al, Si, Ti, Zr, and Ba.

[0147] <7> According to the seventh aspect of the present disclosure,

[0148] An electrode according to any one of the first to sixth aspects is provided, wherein the content ratio of copolymer to inorganic particle [(copolymer) / (inorganic particle)] is 0.1 / 99.9 to 49.9 / 50.1 in mass ratio.

[0149] <8> According to the eighth aspect of the present disclosure,

[0150] An electrode according to any one of the first to seventh aspects is provided, wherein the electrode active material layer contains an electrode active material and a binder, and as the binder, a polymer (except for a copolymer containing a fluoromonomer unit and an amide bond-containing monomer unit).

[0151] <9> According to the ninth aspect of the present disclosure,

[0152] An electrode is provided according to the eighth aspect, which is an electrode active material, and a positive electrode active material.

[0153] <10> According to the tenth aspect of the present disclosure,

[0154] An electrode according to the ninth aspect is provided, wherein the positive electrode active material is a positive electrode active material containing at least one alkali metal selected from the group consisting of Li, Na, and K.

[0155] <11> According to the eleventh aspect of the present disclosure,

[0156] An electrode according to the 9th or 10th aspect is provided, wherein the positive electrode active material comprises at least one alkali metal selected from the group consisting of Li, Na, and K, and at least one metal selected from the group consisting of Fe, Ni, Mn, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si, and Ge.

[0157] <12> According to the 12th aspect of the present disclosure,

[0158] An electrode according to any one of the 9th to 11th aspects is provided, wherein the electrode active material layer also contains a conductive material.

[0159] <13> According to the 13th aspect of the present disclosure,

[0160] When the mass of the electrode active material layer is 100 mass%,

[0161] The content of the positive electrode active material is 80.0 to 99.8 mass%, and

[0162] The content of the conductive material is 0.1 to 10.0 mass%, and

[0163] An electrode according to the 12th aspect is provided, wherein the binder content is 0.1 to 10.0 mass%.

[0164] <14> According to the 14th aspect of the present disclosure,

[0165] An electrode is provided according to the eighth aspect, which is an electrode active material and a negative electrode active material.

[0166] <15> According to the 15th aspect of the present disclosure,

[0167] An electrode according to the 14th aspect is provided, wherein the negative electrode active material is a negative electrode active material containing a carbonaceous material, or a negative electrode active material containing a compound containing at least one element selected from the group consisting of Si, Sn, V, Nb and Ti.

[0168] <16> According to the 16th aspect of the present disclosure,

[0169] When the mass of the electrode active material layer is 100 mass%,

[0170] The content of the negative electrode active material is 99.9 to 80.0 mass%, and

[0171] An electrode according to the 14th or 15th aspect is provided, wherein the binder content is 0.1 to 20.0 mass%.

[0172] <17> According to the 17th aspect of the present disclosure,

[0173] An electrode according to any one of the first to sixth aspects used in an electrochemical device is provided.

[0174] <18> According to the 18th aspect of the present disclosure,

[0175] A secondary battery having an electrode according to any of the first to 17 aspects is provided.

[0176] Examples

[0177] Next, embodiments of the present disclosure will be described with reference to examples, but the present disclosure is not limited to these embodiments.

[0178] Each value of the example was measured by the following method.

[0179] <Monomer Composition of Polymer>

[0180] Using an NMR analyzer (Agilent Technologies, VNS400MHz), 1 H-NMR and 19 The monomer composition of the polymer in a dichloroform solution was measured using F-NMR.

[0181] Weight-average molecular weight

[0182] It was measured by gel permeation chromatography (GPC). It was calculated from data (reference: polystyrene) measured using AS-8010 and CO-8020 from Tosho Co., Ltd., a column (three GMHHR-H connected in series), and RID-10A from Shimadzu Seisakusho Co., Ltd., with dimethylformamide (DMF) flowing as the solvent at a flow rate of 1.0 ml / min.

[0183] In the examples and comparative examples, the following copolymers and inorganic particles were used.

[0184] (Copolymer)

[0185] ·Copolymer a (Composition ratio: Tetrafluoroethylene (TFE) / N-vinyl-2-pyrrolidone (VP)=41 / 59, Weight average molecular weight: 320,000)

[0186] ·Copolymer b (Composition ratio: TFE / VP=38 / 62, Weight average molecular weight: 240,000)

[0187] ·Copolymer c (Composition ratio: TFE / VP=33 / 67, Weight average molecular weight: 97,000)

[0188] ·Copolymer d (Composition ratio: Vinylidene Fluoride (VdF) / Hexafluoropropylene (HFP) = 93 / 7, Weight average molecular weight: 320,000)

[0189] (Inorganic particles)

[0190] · Inorganic Particle X: Aluminum oxide (Particle size: 0.7㎛)

[0191] · Inorganic particle Y: Silicon dioxide (particle size: 0.6㎛)

[0192] · Inorganic particle Z: Zirconium dioxide (particle size: 0.4㎛)

[0193] · Inorganic particle W: Magnesium oxide (Particle size: 0.6㎛)

[0194] Examples 1 to 7, Comparative Examples 1 to 2

[0195] Preparation of Electrolyte

[0196] Ethylene carbonate, a high dielectric constant solvent, and ethylmethyl carbonate and dimethyl carbonate, low viscosity solvents, were mixed in a volume ratio of 30 to 30 to 40, and LiPF6 was added to this to a concentration of 1.1 mol / liter to obtain a non-aqueous electrolyte.

[0197] Production of Straight Drama

[0198] Li(Ni as a positive electrode active material 1 / 3 Mn 1 / 3 Co 1 / 3 A slurry was formed by mixing 5 parts by mass of acetylene black as a conductive material and 5 parts by mass of polyvinylidene fluoride (PVdF) as a binder in an N-methylpyrrolidone solvent. The obtained slurry was applied to one side of a 15 μm thick aluminum foil that had been previously coated with a conductive aid, dried, and roll-pressed with a press machine. The resulting slurry was cut into a shape having an active material layer with a width of 50 mm and a length of 30 mm, and an uncoated section with a width of 5 mm and a length of 9 mm, and used as a positive electrode.

[0199] The Production of the Play

[0200] To 98 parts by mass of a carbonaceous material (graphite), 1 part by mass of an aqueous dispersion of sodium carboxymethylcellulose (concentration of sodium carboxymethylcellulose 1% by mass) and 1 part by mass of an aqueous dispersion of styrene-butadiene rubber (concentration of styrene-butadiene rubber 50% by mass) were added as a thickener and binder, and mixed with a disperser to form a slurry. The obtained slurry was applied to one side of a copper foil with a thickness of 10 μm, dried, and rolled with a press machine. The resulting slurry was cut into a shape having an active material layer with a width of 52 mm and a length of 32 mm, and an uncoated area with a width of 5 mm and a length of 9 mm, and used as a negative electrode.

[0201] The positive electrode obtained above was treated as follows with a composition containing a copolymer and inorganic particles. However, in Comparative Example 2, the positive electrode obtained above was used as is without the following treatment.

[0202] <Coating Treatment (Dip Method)>

[0203] A copolymer and inorganic particles were mixed in the component ratios shown in Table 1, and the resulting mixture was mixed with HFE-347pc-f (CF3CH2OCF2CHF2) to prepare a composition having a solid content of 10 mass%. The positive electrode obtained above was immersed in the composition for 1 minute, and then the immersion was recovered from the composition. The obtained immersion was washed with HFE-347pc-f to wash away deposits attached to the surface of the immersion, and then the washed immersion was dried to obtain a positive electrode having a polymer layer formed on the positive electrode active material layer. It was confirmed that a polymer layer was formed on the active material layer by measuring the thickness or weight using a scanning electron microscope (SEM).

[0204] <Production of Aluminum Laminate Cells>

[0205] A positive electrode having a polymer layer (in Comparative Example 2, a positive electrode not having a polymer layer) and a negative electrode were placed facing each other with a microporous polyethylene film (separator) with a thickness of 20 μm interposed, and the non-aqueous electrolyte obtained above was injected. After the non-aqueous electrolyte sufficiently penetrated the separator, etc., it was sealed and pre-charged and aged to produce a lithium-ion secondary battery (aluminum laminate cell).

[0206] Measurement of Battery Characteristics

[0207] For the obtained aluminum laminate cell, the resistance increase rate after high-temperature storage test and low-temperature cycle test was measured as follows.

[0208] High-temperature storage test

[0209] At 25°C, the battery was charged to 4.35V with a constant current equivalent to 0.2C, and then discharged to 3.0V with a constant current of 0.2C. This was done for two cycles to stabilize the battery, and for the third cycle, the battery was charged to 4.35V with a constant current of 0.2C, then charged with a constant voltage of 4.35V until the current value became 0.05C, and then discharged to 3.0V with a constant current of 0.2C to determine the initial discharge capacity. After that, a storage test was performed by charging to 4.35V with a constant current of 0.2C, and then charging with a constant voltage of 4.35V until the current value became 0.05C.

[0210] Here, 1C represents a current value that discharges the standard capacity of the battery for 1 hour, 5C represents 5 times that current value, 0.1C represents 1 / 10 of that current value, and 0.2C represents 1 / 5 of that current value.

[0211] After the initial characteristic evaluation was completed, the secondary battery in a charged state was stored at a high temperature of 60°C for 672 hours. After cooling the battery sufficiently, it was discharged to 3V at 0.5C at 25°C, then charged to 4.35V with a constant current of 0.2C, charged until the current value became 0.05C with a constant voltage of 4.35V, and discharged to 3.0V with a constant current of 0.2C to determine the storage capacity.

[0212] The dosage retention rate (%) was calculated based on the following formula.

[0213] Capacity retention rate (%) = (Storage capacity) / (Initial discharge capacity) × 100

[0214] <Measurement of Resistance Increase Rate After Low-Temperature Cycle Test>

[0215] At 25°C, the battery was charged to 4.2V with a constant current equivalent to 0.2C, and then discharged to 3.0V with a constant current of 0.2C. This was performed for 2 cycles to stabilize the battery. Subsequently, the secondary battery prepared above was charged to 4.2V with a constant current of 0.2C under an environment of -5°C, then charged with a constant voltage of 4.2V until the current value became 0.05C, and then discharged to 3.0V with a constant current of 0.2C to determine the initial discharge capacity. Charging and discharging were performed in the same manner, and a 200-cycle test was conducted.

[0216] The resistance of the battery at the time of calculating the initial discharge capacity stabilized as described above and the resistance after the cycle test were measured. The measurement temperature was set to -10℃. Based on the following formula, the resistance increase rate after the low-temperature cycle test was calculated.

[0217] Resistance increase rate (%) = Resistance after 200 cycles (Ω) / Resistance after initial discharge capacity calculation (Ω) × 100

[0218] The results are shown in Table 1.

[0219]

[0220] Examples 8 to 14, Comparative Examples 3 to 4

[0221] Preparation of Electrolyte

[0222] Ethylene carbonate and monofluoroethylene carbonate, which are high dielectric constant solvents, and ethyl methyl carbonate, which is a low viscosity solvent, were mixed in a volume ratio of 30 to 5 to 65, and LiPF6 was added to this to a concentration of 1.0 mol / liter to obtain a non-aqueous electrolyte.

[0223] Production of Straight Drama

[0224] 490 mass% of LiMn2O as a positive electrode active material, 5 mass% of acetylene black as a conductive material, and 5 mass% of polyvinylidene fluoride (PVdF) as a binder were mixed in an N-methylpyrrolidone solvent to form a slurry. The obtained slurry was applied to one side of a 15 μm thick aluminum foil that had been previously coated with a conductive aid, dried, and roll-pressed using a press machine. The resulting slurry was cut into a shape having an active material layer with a width of 50 mm and a length of 30 mm, and an uncoated section with a width of 5 mm and a length of 9 mm, and used as a positive electrode.

[0225] The Production of the Play

[0226] To 98 parts by mass of artificial graphite, 1 part by mass of an aqueous dispersion of sodium carboxymethylcellulose (concentration of sodium carboxymethylcellulose 1% by mass) and 1 part by mass of an aqueous dispersion of styrene-butadiene rubber (concentration of styrene-butadiene rubber 50% by mass) were added as a thickener and binder, and mixed with a disperser to form a slurry. The obtained slurry was applied to one side of a copper foil with a thickness of 10 μm, dried, and rolled with a press machine. The resulting slurry was cut into a shape having an active material layer with a width of 52 mm and a length of 32 mm, and an uncoated section with a width of 5 mm and a length of 9 mm, and used as a negative electrode.

[0227] The negative electrode obtained above was treated as follows with a composition containing a copolymer and inorganic particles. However, in Comparative Example 4, the negative electrode obtained above was used as is without the following treatment.

[0228] <Coating Treatment (Dip Method)>

[0229] A copolymer and inorganic particles were mixed in the component ratios shown in Table 2, and the resulting mixture was mixed with HFE-347pc-f (CF3CH2OCF2CHF2) to prepare a composition having a solid content of 10 mass%. The negative electrode obtained above was immersed in the composition for 1 minute, and then the immersion was recovered from the composition. The obtained immersion was washed with HFE-347pc-f to wash away deposits attached to the surface of the immersion, and then the washed immersion was dried to obtain a negative electrode having a polymer layer formed on the negative electrode active material layer. It was confirmed that a polymer layer was formed on the active material layer by measuring the thickness or weight using a scanning electron microscope (SEM).

[0230] <Production of Aluminum Laminate Cells>

[0231] A positive electrode and a negative electrode having a polymer layer (in Comparative Example 4, a negative electrode not having a polymer layer) were placed facing each other with a microporous polyethylene film (separator) having a thickness of 20 μm interposed, and the non-aqueous electrolyte obtained above was injected. After the non-aqueous electrolyte sufficiently penetrated the separator, etc., it was sealed and pre-charged and aged to produce a lithium-ion secondary battery (aluminum laminate cell).

[0232] Measurement of Battery Characteristics

[0233] For the obtained aluminum laminate cell, the resistance increase rate after high-temperature storage test and low-temperature cycle test was measured as follows.

[0234] High-temperature storage test

[0235] At 25°C, the battery was charged to 4.35V with a constant current equivalent to 0.2C, and then discharged to 3.0V with a constant current of 0.2C. This was done for two cycles to stabilize the battery, and for the third cycle, the battery was charged to 4.35V with a constant current of 0.2C, then charged with a constant voltage of 4.35V until the current value became 0.05C, and then discharged to 3.0V with a constant current of 0.2C to determine the initial discharge capacity. After that, a storage test was performed by charging to 4.35V with a constant current of 0.2C, and then charging with a constant voltage of 4.35V until the current value became 0.05C.

[0236] Here, 1C represents a current value that discharges the standard capacity of the battery for 1 hour, 5C represents 5 times that current value, 0.1C represents 1 / 10 of that current value, and 0.2C represents 1 / 5 of that current value.

[0237] After the initial characteristic evaluation was completed, the secondary battery in a charged state was stored at a high temperature of 75°C for 528 hours. After cooling the battery sufficiently, it was discharged to 3V at 0.5C at 25°C, then charged to 4.35V with a constant current of 0.2C, charged until the current value became 0.05C with a constant voltage of 4.35V, and discharged to 3.0V with a constant current of 0.2C to determine the storage capacity.

[0238] The dosage retention rate (%) was calculated based on the following formula.

[0239] Capacity retention rate (%) = (Storage capacity) / (Initial discharge capacity) × 100

[0240] <Measurement of Resistance Increase Rate After Low-Temperature Cycle Test>

[0241] At 25°C, the battery was charged to 4.2V with a constant current equivalent to 0.2C, and then discharged to 3.0V with a constant current of 0.2C. This was performed for 2 cycles to stabilize the battery. Subsequently, the secondary battery prepared above was charged to 4.2V with a constant current of 0.2C under an environment of -10°C, then charged with a constant voltage of 4.2V until the current value became 0.05C, and then discharged to 3.0V with a constant current of 0.2C to determine the initial discharge capacity. Charging and discharging were performed in the same manner, and a 200-cycle test was conducted.

[0242] The resistance of the battery at the time of calculating the initial discharge capacity stabilized as described above and the resistance after the cycle test were measured. The measurement temperature was set to -20℃. Based on the following formula, the resistance increase rate after the low-temperature cycle test was calculated.

[0243] Resistance increase rate (%) = Resistance after 200 cycles (Ω) / Resistance after initial discharge capacity calculation (Ω) × 100

[0244] The results are shown in Table 2.

[0245]

Claims

Claim 1 An electrode comprising an electrode active material layer and a polymer layer formed on the electrode active material layer, wherein the polymer layer comprises a copolymer containing fluoro monomer units and amide bond-containing monomer units and inorganic particles. Claim 2 An electrode according to claim 1, wherein the fluoromonomer is at least one selected from the group consisting of tetrafluoroethylene, hexafluoropropylene, chlorotrifluoroethylene, and 2,3,3,3-tetrafluoropropene. Claim 3 An electrode according to claim 1 or 2, wherein the amide bond-containing monomer has a lactam ring. Claim 4 An electrode according to claim 1 or 2, wherein the amide bond-containing monomer is N-vinyl-2-pyrrolidone. Claim 5 An electrode according to claim 1 or 2, wherein the content of fluoromonomer units of the copolymer is 75 to 7 mol% with respect to the total monomer units, and the content of amide bond-containing monomer units of the copolymer is 25 to 93 mol% with respect to the total monomer units. Claim 6 An electrode according to claim 1 or 2, wherein the inorganic particles contain at least one element selected from the group consisting of Mg, Al, Si, Ti, Zr and Ba. Claim 7 An electrode according to claim 1 or 2, wherein the content ratio of copolymer to inorganic particle [(copolymer) / (inorganic particle)] is 0.1 / 99.9 to 49.9 / 50.1 in mass ratio. Claim 8 An electrode according to claim 1 or 2, wherein the electrode active material layer comprises an electrode active material and a binder, and as the binder comprises a polymer (except for copolymers comprising fluoromonomer units and monomer units containing amide bonds). Claim 9 In paragraph 8, the electrode, wherein the electrode active material is a positive electrode active material. Claim 10 In claim 9, the electrode is a positive electrode active material containing at least one alkali metal selected from the group consisting of Li, Na, and K. Claim 11 An electrode according to claim 9, wherein the positive electrode active material is a positive electrode active material containing at least one alkali metal selected from the group consisting of Li, Na, and K, and at least one metal selected from the group consisting of Fe, Ni, Mn, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si, and Ge. Claim 12 In claim 9, the electrode active material layer also contains a conductive material. Claim 13 An electrode according to claim 12, wherein, when the mass of the electrode active material layer is 100 mass%, the content of the positive electrode active material is 80.0 to 99.8 mass%, the content of the conductive material is 0.1 to 10.0 mass%, and the content of the binder is 0.1 to 10.0 mass%. Claim 14 In paragraph 8, the electrode, wherein the electrode active material is a negative electrode active material. Claim 15 An electrode according to claim 14, wherein the negative electrode active material is a negative electrode active material containing a carbonaceous material, or a negative electrode active material containing a compound containing at least one element selected from the group consisting of Si, Sn, V, Nb and Ti. Claim 16 An electrode according to claim 14, wherein, when the mass of the electrode active material layer is 100 mass%, the content of the negative electrode active material is 99.9 to 80.0 mass% and the content of the binder is 0.1 to 20.0 mass%. Claim 17 An electrode used in an electrochemical device, in paragraph 1 or 2. Claim 18 A secondary battery having the electrode described in paragraph 1 or 2.

Citation Information

Patent Citations

  • Compositions and laminates

    KR1020210041605A